Perubahan Tema dan Perspektif dalam Historiografi Asia Tenggara, 1955-2010 - Sugeng Prakoso (Program Studi Pendidikan Sejarah Pascasarjana UNJ, 2018)
This article examines the changes in themes and perspectives in the writing of Southeast Asian history in the period 1955 to 2010. The historiography of the 1950s tended to political history and the dominant view of the external influences of India, China, Islam, and the West on Southeast Asian history. In the 1960s the thematic focus shifted to economic and social aspects along with the emergence of the trend of social sciences approaches in historical studies which was influenced by the Annales School. In the 1980s, with the onset of the linguistic and cultural turns in the social sciences, historians in the region turned to diachronic studies of the formation of identity, mentality, representation and discourse of local knowledge. The shift in perspective also occurred with the emergence of the (Southeast) Asian-centric perspective which saw changes in Southeast Asian society as a result of the dynamic interaction between the region's internal and external forces. Since the end of the 1990s, there has been a tendency for the ‘interstices’, that is linking the history of the Southeast Asian region with its global historical context, and on the connectivity of historical disciplines with other social-humanities disciplines to build bridges of trans-disciplinary studies.Artikel ini mengkaji perubahan tema dan perspektif dalam penulisan sejarah Asia Tenggara pada periode 1955 sampai 2010. Historiografi dasawarsa 1950-an cenderung pada sejarah politik dan dominannya pandangan ihwal pengaruh eksternal India, Cina, Islam, dan Barat atas sejarah Asia Tenggara. Pada dasawarsa 1960-an fokus tematis bergeser ke aspek ekonomi dan sosial seiring dengan munculnya tren pendekatan ilmu-ilmu sosial yang dipengaruhi oleh Mazhab Annales. Pada dasawarsa 1980-an, dengan menguatnya kajian linguistik dan budaya, sejarawan di kawasan ini beralih ke studi diakronis tentang pembentukan identitas, mentalitas, representasi, dan wacana pengetahuan lokal. Pergeseran perspektif juga terjadi dengan menguatnya perspektif Asia (Tenggara)-sentris yang melihat perubahan-perubahan di dalam masyarakat Asia Tenggara sebagai hasil interaksi dinamis antara kekuatan internal dan eksternal kawasan itu. Sejak akhir dasawarsa 1990-an, muncul kecenderungan pada ‘interstisi’, yaitu menghubungkan sejarah kawasan lokal Asia Tenggara dengan konteks historis globalnya, dan pada konektivitas disiplin sejarah dengan berbagai disiplin ilmu sosial-humaniora lainnya untuk membangun jembatan kajian transdisipliner.